2020
DOI: 10.1159/000506286
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Thrombomodulin in Renal Fibrosis of Nephrotoxic Serum Nephritis in Wistar-Kyoto Rats

Abstract: Background: Recombinant human soluble thrombomodulin (rhTM) was approved in 2008 and has been used for treatment of disseminated intravascular coagulation in Japan. The antifibrotic effects of rhTM in acute exacerbation of idiopathic pulmonary fibrosis are well established, but the therapeutic potential of rhTM in renal fibrosis remains poorly understood. Methods: Nephrotoxic serum nephritis (NTS-N) was induced in 22 female Wistar-Kyoto (WKY) rats on day 0. Rats were administered either rhTM or vehicle intrape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Serum was directly added to the MPCs without activation of complements 44 . Expression of the mouse angiopoietin-like protein 4 (Angptl4), cluster of differentiation (CD)80, NLR family pyrin domain containing 3 (NLRP3), Caspase 1 (Casp1), and GAPDH genes were analyzed using real-time reverse transcription–polymerase chain reaction as previously described 45 . Levels of mouse IL-33 in the supernatant were determined using an ELISA kit (R&D Systems), according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Serum was directly added to the MPCs without activation of complements 44 . Expression of the mouse angiopoietin-like protein 4 (Angptl4), cluster of differentiation (CD)80, NLR family pyrin domain containing 3 (NLRP3), Caspase 1 (Casp1), and GAPDH genes were analyzed using real-time reverse transcription–polymerase chain reaction as previously described 45 . Levels of mouse IL-33 in the supernatant were determined using an ELISA kit (R&D Systems), according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have reported the anti-inflammatory effect of thrombomodulin by inhibiting leukocyte infiltration and suppressing glomerular complement activation in diabetic mice [ 32 , 33 ]. The inhibition of pro-inflammatory and profibrosis of thrombin through the protease-activated receptor pathway is considered an important protective mechanism of thrombomodulin in the kidney [ 34 ]. Pantetheinase and vanin-1 also play a role in the inflammatory process that leads to acute kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…The EnVisionTM+Dual Link System HRP, based on a horseradish peroxidase (HRP)-labeled polymer, was purchased from Dako (Glostrup, Denmark). Immunohistochemical staining for IL-34 (1:100 dilution) and CSF-1 (1:500 dilution) was performed as previously described [31,32]. Similarly, the detailed steps for IHC staining of F4/80 (1:500 dilution) and caspase-3 (1:800 dilution) were described in previous reports [30,33,34].…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%